Flea Infestation of Ctenocephalides felis in Stray Cats and Its Impact on Humans - Tetty Barunawati Siagian; Dyah Prabandari; Aulia Hidayati; Gary Yefta Herbeth Siagian; Muhammad Septo Nasphy (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Infestation by Ctenocephalides felis is a common parasitic problem affecting  both stray and domestic cats worldwide with potential zoonotic impacts on humans. This flea infestation not only affects cats but also poses health risks to humans who come into contact with infested animals. This study aims to investigated the prevalence of C. felis infestation in stray and owned cats in Bogor and its impact on humans and assessed its impact on humans. Methodology: The study was conducted on 20 cats consisting of 9 stray cats and 11 owned cats, were examined using purposes sampling. Physical examinations were performed to detect flea infestation. Fleas were collected and morphologically identified under microscopy. Findings: Results showed an overall prevalence of 90% with details 100% in stray cats and 82% in domestic cats. Clinical signs in cats included symmetrical alopecia, anemia, dull coat, and low body condition score. Human cases associated with flea infestation presented red papules, itching, and discomfort. Contributions: This study represents the first documented prevalence of C. felis in cats and associated human impacts in Bogor, highlighting its veterinary and public health importance